2012
DOI: 10.1002/jwmg.320
|View full text |Cite
|
Sign up to set email alerts
|

Hot moments and hot spots: Identifying factors explaining temporal and spatial variation in turtle road mortality

Abstract: Many conservation strategies focus on reducing the risk of road mortality. Turtles, which are highly susceptible to road mortality, exhibit life history traits that increase their vulnerability to population declines because of road mortality. Here, we use Akaike's Information Criterion to identify road mortality hot moments and hot spots for 5 turtle species (Chelydra serpentina, Pseudemys concinna, Terrapene carolina, Terrapene ornata, and Trachemys scripta). We tested 2 hypotheses: 1) Hot moments coincide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…The importance of vehicles as a mortality source across a range of terrestrial taxa is shown in Table 8.1. In some cases, vehicle mortality is so high that it represents the greatest limitation to population growth, and may exceed reproduction, such as for black bears (Beckmann and Lackey 2008) and some reptiles (Cureton and Deaton 2012). Some turtle species are highly susceptible to road mortality because they are not able to adjust or avoid road traffic, and their relatively low fecundity does not allow for replacement of individuals killed by cars.…”
Section: Roadsmentioning
confidence: 98%
See 1 more Smart Citation
“…The importance of vehicles as a mortality source across a range of terrestrial taxa is shown in Table 8.1. In some cases, vehicle mortality is so high that it represents the greatest limitation to population growth, and may exceed reproduction, such as for black bears (Beckmann and Lackey 2008) and some reptiles (Cureton and Deaton 2012). Some turtle species are highly susceptible to road mortality because they are not able to adjust or avoid road traffic, and their relatively low fecundity does not allow for replacement of individuals killed by cars.…”
Section: Roadsmentioning
confidence: 98%
“…Some turtle species are highly susceptible to road mortality because they are not able to adjust or avoid road traffic, and their relatively low fecundity does not allow for replacement of individuals killed by cars. Turtle populations affected by road mortality are those that are male biased and occur at low densities (Cureton and Deaton 2012).…”
Section: Roadsmentioning
confidence: 99%
“…Finally, the development and use of models continues to gain popularity with a further nine studies presenting models that could be used to estimate road-related mortality [134,135] and identify potential mortality hotspots based on surrounding habitat and landscape features [40,[136][137][138][139]. For example, one model was constructed specifically to identify ideal locations for crossing structures for the endangered Florida panther (Puma concolor coryi) using GPS collar data and wildlife-vehicle collision reports [140].…”
Section: Survey Design and Mitigationmentioning
confidence: 99%
“…Previous studies have demonstrated condensed patterns of road mortality at relatively broad spatial and temporal scales and have advocated that such broad hot spots or hot moments could improve management for road mortality (Grilo, Bissonette & Santos‐Reis ; Beaudry, Demaynadier & Hunter ; Cureton & Deaton ). Our results demonstrate that even finer‐scale hot spots and hot moments can be identified and related, strongly or weakly, to specific habitat features or temporal processes.…”
Section: Discussionmentioning
confidence: 99%